Expression of Nogo receptor 1 in the regeneration process of the mouse olfactory epithelium. Issue 10 (6th July 2016) - Chen, He-Xin; Zeng, Xian-Ping; Sun, Yue-Qi; Fu, Qing-Ling
Abstract : Nogo receptor 1 (NgR1) is the most important Nogo-A receptor. By its interaction with myelin-associated inhibitory proteins, NgR1 inhibits the regeneration of axons and is extensively expressed in the central nervous system. However, the expression of NgR1 in regenerable neurons, such as olfactory neurons, and its expression in the regeneration progress of olfactory neurons have not been reported. In this study, we demonstrated that NgR1 was expressed in the cell bodies of certain mature olfactory receptor neurons (ORNs) but was not expressed in immature ORNs in the olfactory epithelium (OE) of normal adult mice. On day 21 after OE injury, NgR1 was expressed not only in the cell bodies of mature ORNs but also in the cell bodies of glial fibrillary acidic protein (GFAP)-positive cells in the top and submucosal layers of the OE. On day 48 after model establishment, NgR1 expression decreased in the cell bodies of the GFAP-positive cells. On day 56 after model establishment, no NgR1 expression was found in the cell bodies of the GFAP-positive cells, and NgR1 was again expressed only in the mature ORNs. Our results demonstrated that NgR1 expression is upregulated in the OE after injury, which suggests that NgR1 might be involved in the regeneration of the OE.